Phenomenology today: the challenge of naturalism - Botero, Juan José (Estudios de Filosofía, 1999)
The author looks for sketching the problem that Husserlian phenomenology would have to face today if confronted witlz the, so-called, cognitive sciences that have recently appeared. Such confrontations can be viewed as a) tlze breaking in ofan antagonic perspective on some topics of Husserl Phenomenology, or b) as an acceptance that the new scientific realities, shown by cognitive sciences, open the possibility of naturalizing some descriptions that were provided by the phenomenology. For the author of the paper, the latter looks more promising.